Students as Propulsion Engine of Medical Education System: The Concept of the Student Committee of Medical Education Development - AmirAli Moodi Ghalibaf; Hamid Yazdaninejad; Radman Amiri; Amir Hossain Karimi; Zahra Safari; Ali Akbar Khosravi-Larijani; Keivan Lashkari; Amir Mohammad Parsanahad; Mohammad Javad Ghapanchian; Sina Yousefian; Ali Madadi-Mahani; Ali Mohammad-Hassani; et al. (Strides in Development of Medical Education)
Dear Editor,From the past decades to the present, medical education has been known as one of the most important fields of education which trains those who can, directly and indirectly, affect human health and lives (1). Despite medical education being divided into various sectors, its ultimate aim is to “supply society with knowledgeable, skilled, and up-to-date health profession providers who put patient care above self-interest, and who undertake to maintain and develop their expertise over the course of a lifelong career”. Therefore, medical education is imagined as a busy, clamorous place, where a host of pedagogical practices, educational philosophies, and conceptual frameworks collide (2).....